1972
DOI: 10.1152/ajplegacy.1972.223.3.715
|View full text |Cite
|
Sign up to set email alerts
|

Surface active materials from dog lung. II. Composition and physiological correlations

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
145
1
7

Year Published

1979
1979
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 512 publications
(160 citation statements)
references
References 0 publications
7
145
1
7
Order By: Relevance
“…Therefore, infants may be dependent on nutritional sources of carnitine, such as milk. Infants receiving carnitine-free total parenteral nutrition are at risk of developing carnitine deficiency characterized by decreased blood concentration and tissue content of carnitine (2, 20,24,28). Reduced carnitine intake may impair fatty acid oxidation and diminish ketogenesis after fat infusion; these deficiencies can be corrected with supplementary carnitine (23,29).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, infants may be dependent on nutritional sources of carnitine, such as milk. Infants receiving carnitine-free total parenteral nutrition are at risk of developing carnitine deficiency characterized by decreased blood concentration and tissue content of carnitine (2, 20,24,28). Reduced carnitine intake may impair fatty acid oxidation and diminish ketogenesis after fat infusion; these deficiencies can be corrected with supplementary carnitine (23,29).…”
Section: Discussionmentioning
confidence: 99%
“…The mucociliary transport rate was expressed as an average of the total measure ment during a 10 min period after ACh nebulizing (control) and during a 10 min period after acid-nebulizing, respectively. The composition of surface active phospholipids shown in Table 1 was based on the concen trations of those in pulmonary surfactant (11,12 2. Effect of ACh on mucociliary transport: Nebulizing ACh caused an approximately 70% increase in the mucociliary transport rate, and the increase lasted for 50 min (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…SP-A and SP-D may play important roles in the first line defense against inhaled pathogens, and SP-A may have a regulatory function in the formation of the monolayer that lowers the surface tension. In 1972 King and Clements reported that canine surfactant lipids were able to form stable surface films with low surface tension but that this process was much faster when complete canine surfactant with the proteins included was used [170]. This important observation indicated that the presence of the surfactant-associated proteins was required for an optimal functioning of the lung.…”
Section: Composition Of Surfactantmentioning
confidence: 99%